Effect of the Implant Length on its Primary Stability - L. Dzan; L. Čapek (Czech Dental Chamber, 2009)
Dental implantology is one of the fastest developing areas of stomatology. An implantologists needs to have good quality medically proven information so that they can provide the best care for the patience from what today's science and market offers. Long term correct functioning of the implants is influenced by their design (size, surface, diameter and length) and surgical procedure of the implantation. The subject of this work is the evaluation of the influence of the length of the implant on its primary stability measured by Resonance Frequency Analysis (RFA) and a resulting set of parametric calculations with using the method of the sinite elements.